Agricultural productivity shocks and poverty in India: The short- and long-term effects of monsoon rainfall - Björn Brey; Matthias S. Hertweck (Deutsche Bundesbank, 2019)
This paper examines the dynamic effects of monsoon rainfall shocks on yield, wages, and prices in the Indian agricultural sector. We distinguish between positive and negative rainfall shocks and explicitly consider their spatial dimension (local/regional). We find that particularly negative regional shocks exert adverse effects. The enormous drop in agricultural yield is short-lived, but elicits a persistent decline (increase) in wages (food prices). Negative local shocks affect only wages, but not prices. This indicates that, in the food market, intra-regional trading mitigates the impact of local shocks. However, in the labour market, the arbitrage mechanism through migration appears substantially weaker.
Keywords: C33; E32; O13; Q11; 330; rainfall shocks; agricultural yield; wages; food prices